Building a Police Service in Challenging and Changing Times - Jennifer Hyland (The Journal of Intelligence, Conflict and Warfare, 2022)
On November 25, 2021, Deputy Chief Cst. Jennifer Hyland, with the Surrey Police Service (Canada), presented on Building a Police Service in Challenging and Changing Times at the 2021 CASIS West Coast Security Conference. The presentation was followed by a question and answer period with questions from the audience and CASIS Vancouver executives. The key points discussed included the development of a new policing service in a developing city with a diverse community such as Surrey, community policing, and practicing a healthy policing culture within the police force in order for it to be reflected externally in the community.